ANALISIS METODE PRESERVASI SUBKULTUR BERKALA DAN DENGAN AIR STERIL UNTUK JAMUR Aspergillus sp. DAN Candida albicans - Gabi Vania Sally; Sandy Vitria Kurniawan; Sem Samuel Surja (Bahasa Indonesia, 2020)
Introduction: A good and proper preservation can maintain all collection of culture. Periodic subculture preservation is an old technique that is less able to guarantee the genetic characteristic for a long time. Sterile water is an alternative method in various studies to ensure the genetic characteristic for a long time and can be done in a simple laboratory concept. This study aimed to examine the method of periodic subculture and with sterile water Methods: This research was a descriptive study with an experimental laboratory design on Aspergillus sp. and Candida albicans. This study examined at periodic subculture methods and with sterile water in maintaining viability, level of contamination, morphology, and antifungal resistance after six months Results: The fungus had lived after being preserved with periodic subcultures without contamination, morphological changes, and resistance. Aspergillus sp. and Candida albicans also lived after being preserved with sterile water for six months with the same morphology and without contamination. The zone of inhibition of Aspergillus sp. had decreased but in Candida albicans remains the same. Conclusion: Preservation with periodic subculture and with sterile water can be applied to Aspergillus sp. and Candida albicans.